Onigamiising : Seasons of an Ojibwe Year - Grover, Linda LeGarde (Book collections on Project MUSE., 2017)
Long before it came to be known as Duluth, the land at the western tip of Lake Superior was known to the Ojibwe as Onigamiising, "the place of the small portage." There the Ojibwe lived in keeping with the seasons, moving among different camps for hunting and fishing, for cultivating and gathering, for harvesting wild rice and maple sugar. In Onigamiising Linda LeGarde Grover accompanies us through this cycle of the seasons, one year in a lifelong journey on the path to Mino Bimaadiziwin, the living of a good life. In fifty short essays, Grover reflects on the spiritual beliefs and everyday practices that carry the Ojibwe through the year and connect them to this northern land of rugged splendor. As the four seasons unfold--from Ziigwan (Spring) through Niibin and Dagwaagin to the silent, snowy promise of Biboon--the award-winning author writes eloquently of the landscape and the weather, work and play, ceremony and tradition and family ways, from the homey moments shared over meals to the celebrations that mark life's great events. Now a grandmother, a Nokomis, beginning the fourth season of her life, Grover draws on a wealth of stories and knowledge accumulated over the years to evoke the Ojibwe experience of Onigamiising, past and present, for all time.